Is the 32-kDa fragment the functional enamelin unit in all species? - Brookes, Steven J (Blackwell Publishing Ltd, 2011)
Enamelin is an extracellular enamel matrix protein essential for normal amelogenesis. After secretion, porcine enamelin is processed to generate several enamelin-degradation products. The cumulative 32-kDa enamelin is the most abundant enamelin present, and various roles for this molecule have been suggested. However, the proteolytic cleavage sites in porcine enamelin that generate the 32-kDa enamelin are not conserved across species, and the 32-kDa enamelin analogue may not be present in all species. To explore this we studied rat enamelin biochemistry using western blotting with anti-peptide IgGs to porcine 32-kDa enamelin and to the putative rat 32-kDa enamelin analogue. The dominant enamelins in secretory-stage rat enamel migrated at around 60–70 kDa. In contrast, the dominant enamelins in secretory-stage porcine enamel migrated at around 32 kDa. In contrast, secretory-stage porcine-enamel enamelins were dominated by the 32-kDa enamelin. Rat enamelin was completely removed from maturation-stage enamel without any accumulation of 32-kDa enamelin. We suggest that a discrete 32-kDa enamelin is not essential for normal amelogenesis in all species, and in pig it may be a processing product of a larger functional enamelin molecule. The pig may be an atypical model in terms of enamelin biochemistry and function, and caution should be exercised when assigning functional roles to the 32-kDa enamelin as a discrete enamel matrix entity.